2016
DOI: 10.1590/1678-4324-2016150010
|View full text |Cite
|
Sign up to set email alerts
|

Bromelain: Methods of Extraction, Purification and Therapeutic Applications

Abstract: Bromelain is a concoction of sulfhydryl proteolytic enzymes. Depending upon the site of extraction it can be regarded as either stem bromelain (SBM) (EC 3.4.22.32) or fruit bromelain (FBM) (EC 3.4.22.33

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 63 publications
(101 reference statements)
1
57
0
2
Order By: Relevance
“…Bromelian active at pH 3 through to pH 7 where it activity is at maximal until it finaly falls at pH 8 for all parts of the pineapple. Corzo et al, [24] and Manzoor et al, [25] support the result as it was reported that bromelain act well within pH range 3 -8. Beyond this pH value, the activity declined progressively.…”
Section: Figure 6 Effect Of Bromelain On Bromelain Activity Obtainedsupporting
confidence: 56%
“…Bromelian active at pH 3 through to pH 7 where it activity is at maximal until it finaly falls at pH 8 for all parts of the pineapple. Corzo et al, [24] and Manzoor et al, [25] support the result as it was reported that bromelain act well within pH range 3 -8. Beyond this pH value, the activity declined progressively.…”
Section: Figure 6 Effect Of Bromelain On Bromelain Activity Obtainedsupporting
confidence: 56%
“…Also, Rathnavelu, Alitheen, Sohila, Kanagesan, and Ramesh, () show that bromelain remains biologically active with a half‐life of 6–9 hr in human body. The enzymatic activity of bromelain covers a wide pH spectrum from 5.5 to 8.0 (Pavan, Jain, Shraddha, & Kumar, ), while the optimum range is 6.0–7.0 at a temperature range of 50–60 ◦ C (Manzoor, Nawaz, Mukhtar, & Haq, ). There are many studies were carried out to investigate the separation, extraction and purification of bromelain from pineapple residues (Coêlho, Silva, Machado, Silveira, & Tambourgi, ; Ketnawa, Chaiwut, & Rawdkuen, ; Martins et al, ; Novaes, Ebinuma, Mazzola, & Júnior, ).…”
Section: Introductionmentioning
confidence: 99%
“…Filtering and enter into the bottle Sardine Sauce Fig. 1 Flow chart of producing sardine sauce using bromelain enzyme J Food Sci Technol methods (Ketnawa et al 2011;Manzoor et al 2016): five mature pineapple fruit was weighed, cleaned well-using water, and crushed into small pieces. Then, adding sodium acetate buffer into it, and the extract was homogenized and filtered by using a fine cloth.…”
Section: Methodsmentioning
confidence: 99%